PENYELESAIAN TINDAK PIDANA RINGAN MELALUI PROSES KEARIFAN LOKAL SEBAGAI BAGIAN DARI RESTORATIVE JUSTICE - Des Maicho Elwin; Pasolang Pasapan; Edgar Michael Parinussa (Paulus Law Journal, 2022)
Restorative justice in the criminal justice system is justice whose process involves all parties in a particular crime and jointly solve problems and deal with future consequences. One way that can be used is to consider the local wisdom that exists in an area. This study aims to find out how the process of resolving minor crimes through the process of Local Wisdom as part of Restorative Justice in the Wasuponda community, especially the Padoe custom and being able to find out what are the obstacles faced by the customary council and law enforcement officers in resolving minor crimes through the wisdom process. as part of restorative justice in the Wasuponda community. This study uses a normative-empirical research method. The data used in the research is secondary data (Library Research) in the form of laws, books, journals, and scientific articles related to the title, then primary data for field research (Field Research) based on interviews with the Padoe customary council. . The data obtained were then analyzed by the author in a descriptive-qualitative manner. The results of the study indicate that the process of Local Wisdom as part of restorative justice in the community with Padoe Customs in Wasuponda has been carried out for a long time. The Wasuponda Sector Police coordinates with the Padoe Customary Council in dealing with minor crimes as a fair, fast and low-cost decision. To support the sustainability of the implementation of justice with local wisdom, it is necessary to socialize to the community regarding the process of resolving minor crimes in local wisdom as part of restorative justice so that there is understanding in the community.